PENGEMBANGAN LKPD MENULIS TEKS CERAMAH BERBASIS PROJECT BASED LEARNING PADA SISWA KELAS XI SMA SWASTA BAITUL AZIZ DELI SERDANG - Widya Utami; Rina Devianty; Edi Saputra (Academic Solution Publisher, 2026)
This study aims to develop a Student Worksheet (LKPD) for writing lecture texts based on Project-Based Learning (PjBL) in Indonesian language learning for eleventh grade. The background of this research is the low level of lecture writing skills among students and the limited availability of teaching materials that support active learning. The development was conducted using the Research and Development (R&D) method, which included needs analysis, product design, development, expert validation, and limited trials. Subjects in this study included material experts, language experts, media experts, Indonesian language teachers, and eleventh grade students. Data collection was conducted using a validation questionnaire, a practicality questionnaire, and a learning outcome test. The findings indicate that the resulting LKPD has a very high feasibility level, with a percentage of 96.66%. The effectiveness test results showed an N-Gain value of 0.71 in the experimental class (high category), while the control class had a score of 0.25 (low category). Furthermore, the practicality level was very high, indicated by a percentage of 98% of teachers and 84.6% of students. Based on these results, the Project-Based Learning (LKPD) worksheet is deemed feasible, effective, and practical for use in Indonesian language learning for 11th grade.